Electrical Stimulations of the Human Insula: Their Contribution to the Ictal Semiology of Insular Seizures. Issue 4 (July 2017) - Mazzola, Laure; Mauguière, François; Isnard, Jean
Abstract : Introduction: Stereotactic stimulations of the insular cortex through intracranial electrodes aim at characterizing the semiology of insular seizures. These stimulations, carried out in the context of Stereo-Electro-Encephalography (SEEG) during presurgical monitoring of epilepsy, reproduce the ictal symptoms observed during the development of insular seizures. Methods: The authors reviewed the results of insular stimulations performed in 222 patients admitted between 1997 and 2015 for presurgical SEEG exploration of atypical temporal or perisylvian epilepsy. Stimulations (50 Hz, trains of 5 seconds, pulses of 0.5 ms, intensity 0.2–3.5 mA) were carried out using transopercular electrodes implanted orthogonal to midsagittal plane. Results: Out of a total of 669 stimulations, 550 were clinically eloquent in the absence of any postdischarge (237 and 313, respectively, in the right and left insulae). Somatosensory responses (61% of evoked sensations) including pain and visceral sensations (14.9%) were the most frequent, followed by auditory sensations (8%), vestibular illusions (7.5%), speech impairment (5%), gustatory, (2.7%), and olfactory (1%) sensations. Although these responses showed some functional segregation (in particular a privileged pain representation in the postero-superior quadrant), there was a clear spatial overlap between representations of the different modalities. Conclusions: Symptoms evoked by insular stimulations are multiple. None of them can be considered as absolutely specific to the insular cortex, but the occurrence in given seizure of a somatosensory symptom such as pain or of a laryngeal spasm associated with vestibular, auditory, aphasic, or olfacto-gustatory symptoms points to a discharge development in the insular cortex, which is the only cortical region where stimulations demonstrate such a multimodal representation.